Nanoparticle-facilitated targeted nutrient delivery in plants: Breakthroughs and mechanistic insights - Meena Yadav (Plant Nano Biology)
Nanofertilizers (NFs) possess unique properties such as enhanced adhesion to minimize nutrient loss, and slow and controlled nutrient release, that not only enhance plant growth and increase yield but also enable them to ameliorate stress conditions. These properties have been instrumental in addressing the drawbacks of conventional fertilizers. While NFs began to be synthesized in early 2000s, emphasis was laid on synthesis of inorganic NFs during 2010–2020. In the past decade, there have been advancements in the methods of NF synthesis, such as synthesis of metal and metal oxide NFs; synthesis of nano-composites using hydroxyapatite (HA), silica, zeolite and graphene oxide; loading of nutrients onto layered double hydroxides, and chitosan; synthesis of chelated NFs; synthesis of 2-D nano-formulations and 2-D NFs; synthesis of organic NFs using biopolymers and agricultural waste; and synthesis of nano-biofertilizers. This review primarily explores these recent advancements for targeted nutrient delivery within plants and their mechanisms of action, potential of NFs to ameliorate stress such as drought, salinity and metal toxicity to improve crop yield, and factors affecting NFs facilitated nutrient delivery. An integrated approach that uses conventional fertilizers along with NFs, tailor-made for different soil types, and use of artificial intelligence to regulate the release of fertilizers would be an ideal approach to improve plant health and increase yield, with minimal environmental impact. This review provides insights and directions for future research to address plant nutrition under stress and nutrient deficiency conditions.